Análise da implementação da política de turismo na região de negócios e tradições em Goiás (2008-2014) - Jesus, Rassan Solarevisky de (2016)
From proper planning and effective implementation of a public policy for the development of tourism, this sector can contribute to economic and social development of a region. This research aimed to identify and analyze the factors involved in the implementation of tourism policy in Business and Traditions Region in the State of Goiás, between 2008 and 2014. The research took advantage of the qualitative approach and the study only if the method for its operation, which concluded that there was a low degree of implementation of the programs and actions in the documents that guide the tourism policy in the region studied: Integrated Development Plan for Sustainable Tourism (2012), Business Plan (2008) Tourism Municipal plans Goiania, Anapolis and Trinity Marketing Plan. The factors identified for this are: the political games established in the trading networks; the alternation of power; not specifying the technical, human and financial; the implementation of actions, projects and strategies of top-donw way, besides a very incipient intersectoriality the management of public policy tourism process process in the region Business and Traditions. Suggested some alternatives with a view to greater success in implementing this type of policy, such as: management of more interactive policy between the actors, the articulation between the regional and municipal plans, greater private sector participation in the management of tourism policies ; and even a better specification of the human, technical and financial resources for each proposed action.